PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUKMENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 25 PAKNING ASAL KECAMATANBUKIT BATU KABUPATEN BENGKALIS - Andriani, Andriani; Antosa, Zariul; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research aims to improve Mathematics learning outcomes fourth grade students of SDN 25 Pakning Asal Kecamatan Bukit Batu Kabupaten Bengkalis academic year 2014/2015. The improvement of studentsmathematics learning outcomes can be seen through the